Islam dan Globalisasi: Formulasi Solutif terhadap Krisis Identitas Muslim - Muhammad Ikhsan; Azwar Azwar (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research was conducted with the aims of: knowing the meaning of globalization; (2) knowing and analyzing the negative impact of globalization on the identity of the nations; and (3) knowing and analyzing solutions to confront the impact of globalization towards muslim identity. This research used qualitative descriptive approach with library research method. The sources of this research data are books related to the history and development of globalization. The results show that: (1) globalization means bringing the world closer together through great advances in communication, transportation, satellites and the internet, openness of information flows, accompanied by one-pole power (in this case America with its influence of Zionism) that seeks to unite all economic, political forces (including the military) and thought to fulfill its interests; (2) the negative impact of globalization on the nations of the world, especially in the Islamic world, is that globalization has a high potential in reshaping the basic understandings of Muslims about nature, people and life, to be replaced by the understanding that has been commonly believed in the West; and (3) Islam and muslims can actually use globalization as an effective way to strengthen their identity. The use of globalization in order to affirm the identity of Islam and muslims is of course based on the objective view that this phenomenon does not fully contain negative values and holds a very powerful force, depending on "who and how" it is utilized. The beautiful collaboration between scholars, thinkers, scientists, experts, culturalists, and muslim perpetrators of globalization in formulating elements of globalization appropriately is an expectation for the strengthening of muslim identity in the midst of the current globalization.